Improving Students Listening Ability Through Application Of Audio-Visual At Smpn 2 Painan - Nurmalinda Nurmalinda (Jurnal Ilmiah Pendidikan Scholastic, 2017)
In order to learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do", which describe something in their own way, showing for example, tried to practice skills and tasks that require p What Knowledge they have earned. Problems to be studied in this research are: (1) pakah using Audio-Visual models in class IX students of SMP Negeri 2 Painan years 2015-2016? (2) angkah - steps involved in using the method of applying the Audio-Visual? Knowing that trigger low activity of learning and learning achievement exist on factors such as the method used by the teacher, so that the use or replacement of conventional methods into methods that are constructivist indispensable, consequently researchers tried learning model Audio-Visual in an attempt to solve Problems that exist in school. The low activity of learning and student achievement were presented at the background of the problem, the use of Audio-Visual learning model strived to be able to complete the purpose of this study is to determine the improvement of student achievement. How much improvement has been made clear at the end of the analysis. From the results of the research presented in Chapter IV and all the data that have been submitted, the research objectives submitted can already be achieved. To answer the research objectives namely the achievement of the increase in student learning achievement can be seen the evidence already disampaikan. From preliminary data nearly all students scored at the bottom, then the first cycle decreased to 8 students and second cycle the value of all the students on the school specified standards . From the initial average 4.5 rose to 6.3 in the first cycle and the second cycle increased to 7.9. From the preliminary data there are no students who completed while the first cycle to more that four students and the second cycle all students achieve mastery. Of all supporting data proving the achievement of learning objectives could be said that the model Audio-Visual can give the expected answer to the purpose of this research. All this can be achieved is due to the readiness and hard work of researchers from the start of the proposal, review the things that have not been good with my friends teachers, preparation of grids and research instruments, the use of means of data triangulation to the implementation of the maximum research.